2018
DOI: 10.4103/ijd.ijd_351_17
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic yeasts recovered from acne vulgaris: Molecular characterization and antifungal susceptibility pattern

Abstract: Context:Acne vulgaris is a disorder showing persistent inflammation in the pilosebaceous follicles. It is one of the most prevalent dermatoses that millions of people suffer from globally.Aim:The aim of this study was to identify Candida species from patients with acne and to determine their drugs susceptibility.Subjects and Methods:A total of 70 cutaneous samples from acne vulgaris patients suspected to have Candida infections were collected. Macroscopic and microscopic morphology were recorded followed by po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Malassezia species, and more recently Candida species, have also been implicated in acne pathology, causing well-documented cases of folliculitis [63,64,65,66,67,68]. However, researchers are usually careful not to call yeast-associated folliculitis “acne”, due to the perception that acne vulgaris includes other clinical findings such as comedones that are not typically found in yeast-associated folliculitis.…”
Section: Disease-specific Changesmentioning
confidence: 99%
“…Malassezia species, and more recently Candida species, have also been implicated in acne pathology, causing well-documented cases of folliculitis [63,64,65,66,67,68]. However, researchers are usually careful not to call yeast-associated folliculitis “acne”, due to the perception that acne vulgaris includes other clinical findings such as comedones that are not typically found in yeast-associated folliculitis.…”
Section: Disease-specific Changesmentioning
confidence: 99%
“…For 32 of those 45 studies, no potential safety concern was reported, while a potential safety concern was described in the other 13 studies (corresponding to 11 articles: Diba et al., ; Das et al., ; Jung et al., ; Kara et al., ; Khedri et al., ; Nagy et al., ; Omran and Mansori, ; Sadrossadati et al., ; Afsarian et al., ; Shokohi et al., ; Teblick et al., ): 3 for C. famata (Das et al., ; Diba et al., ; Shokohi et al., ), 7 for C. kefyr (Afsarian et al., ; Diba et al., ; Khedri et al., ; Nagy et al., ; Omran and Mansori, ; Sadrossadati et al., ; Shokohi et al., ), 1 for C. pelliculosa (Jung et al., ) and 2 for Saccharomyces cerevisiae (Kara et al., ; Teblick et al., ). All these studies reported isolation of the QPS yeasts from opportunistic infections in patients with serious predisposing factors.…”
Section: Assessmentmentioning
confidence: 99%
“…These 30 articles included description of 45 studies related to different yeast species with QPS status, of which 16 referred to Candida kefyr (teleomorph = Kluyveromyces marxianus ) (Afsarian et al., ; Awad et al., ; Bharathi, ; Diba et al., ; García‐Agudo et al., ; Hasan and Yassein, ; Kaur et al., ; Kesmen et al., ; Khedri et al., ; Nagy et al., ; Okmen et al., ; Omran and Mansori, ; de Paula et al., ; Sadrossadati et al., ; Shokohi et al., ; Simi et al., ), 8 to Saccharomyces cerevisiae including Saccharomyces boulardii (corresponding to 7 articles: Lazo‐Vélez et al., ; Ruelle et al., ; Hasan and Yassein, ; Kara et al., ; Kesmen et al., ; Ochiai et al., ; Teblick et al., ), 10 to Candida famata (teleomorph = Debaryomyces hansenii ) (Afsarian et al., ; Alobaid and Khan, ; Awad et al., ; Cen et al., ; Das et al., ; Diba et al., ; Hasan and Yassein, ; Kesmen et al., ; de Paula et al., ; Simi et al., ), 6 to Candida pelliculosa (synonymus = Pichia anomala , teleomorph = Wickerhamomyces anomalus ) (Ahmadsah et al., ; Arendrup et al., ; Cen et al., ; Jung et al., ; Kesmen et al., ; Soman et al., ), 1 to Candida utilis (teleomorph = Lindnera jadinii ) (Treguier et al., ), 1 to Hanseniaspora uvarum (Kesmen et al., ), 1 Kluyveromyces lactis (Kesmen et al., ) a nd 1 to Schizosaccharomyces pombe (Kesmen et al., ). One of these articles was considered relevant (Pfaller et al., ) to evaluate since it presented new data on antimycotic MIC breakpoints for azoles but it is not associated to any specific yeast TU.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors such as changing seasons and changing habits are among the risk of antifungal resistance. Most of resistance C. albicans cases are the major factors of defeated sequential treatment which most of them are resistant to common antifungal drugs, itraconazole, fluconazole and ketoconazole (Omran and Mansori, 2018).…”
Section: Introductionmentioning
confidence: 99%